Blood 2, 5-dimethyfuran as a sensitive and specific biomarker for cigarette smoking. (September 2014) - Jia, Chunrong; Ward, Kenneth D.; Mzayek, Fawaz; Relyea, George
Abstract Objective: We evaluated the validity of blood 2, 5-dimethylfuran (DMF) for determining smoking status using population-based data. Methods: We obtained blood DMF concentrations and smoking status from National Health and Nutrition Examination Survey 2003–2006 and computed sensitivity, specificity and Kappa statistic. Results: Self-reported smoking showed very high agreement (Kappa = 92.8–93.3%) in daily smokers and fair agreement in non-daily smokers (Kappa = 33.7–36.4%). Coffee intake did not influence the detection of blood DMF. Conclusions: Blood DMF has comparable sensitivity and specificity with serum cotinine for identifying current daily smokers, which may make it a useful biomarker in epidemiologic studies.